2015
DOI: 10.18052/www.scipress.com/ilshs.63.218
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Assertiveness Skills on Job Burnout

Abstract: ABSTRACT. Assertiveness is the ability to express oneself and one's rights without violating the rights of others. The need for assertiveness is widely acknowledged in different work settings, and in order to manage the stress of working as part of a team every day, one has to become assertive. The purpose of present study is to investigate the effect of assertiveness skills on job burnout. The random sampling technique was employed. The data were gathered from 100 respondents. The adapted questionnaire was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…In fact, high WBC count is strongly associated with metabolic syndrome in rat, 21 and human. 22,23 White blood cell count was significantly positively correlated with body mass index, the expression of an insulin-resistant state or involvement of the MS (Nakanishi, 2004;Park, 2009). And, an increase in the WBC count with the MS could be due to the presence of lymphocytes and monocytes in this inflammatory reaction (Figs: lymphocyte and Monocyte).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, high WBC count is strongly associated with metabolic syndrome in rat, 21 and human. 22,23 White blood cell count was significantly positively correlated with body mass index, the expression of an insulin-resistant state or involvement of the MS (Nakanishi, 2004;Park, 2009). And, an increase in the WBC count with the MS could be due to the presence of lymphocytes and monocytes in this inflammatory reaction (Figs: lymphocyte and Monocyte).…”
Section: Discussionmentioning
confidence: 99%
“…The study's findings revealed a significant link between emotional exhaustion and decreased engagement, and this, in turn, was associated with an increase in reports of action errors and violations [64]. Prior research on the subject of burnout has primarily revolved around the origins of the burnout syndrome, given its implications for the mental well-being of employees and its adverse effects on the quality of services delivered by these individuals [65,66].…”
Section: %mentioning
confidence: 93%
“…Using this procedure, the assertive subjects were selected in the study. 3 To describe the types of people's behavior in conflicts and their quantitative assessment, K. Thomas's test was used (adapted by NV Grishina), 23 which reveals the behavior strategies of the subject in the conflict. The test implements a twodimensional model of K. Thomas dealing with conflict resolution, which reveals the relationship between a person's taking into account the interests of other people involved in the situation and an emphasis on his own interests.…”
Section: Methodical Toolsmentioning
confidence: 99%
“…Butt A & Zahid Z 23 showed that assertive skills reduce burn-out at work, which contributes to satisfaction with it. With the increase in the level of assertive skills, coherence and trust increase, the severity of conflicts and stresses decreases, which also leads to a reduction in burnout.…”
mentioning
confidence: 99%